Enhancing detection of STEC in the meat industry: insights into virulence of priority STEC - Tran, Mai-Lan; Delannoy, Sabine; Fach, Patrick (Frontiers in Microbiology, 2025)
Detection of Shiga toxin-producing Escherichia coli (STEC) presenting high risk of human infections is challenging. In France, the latest Anses opinion categorized STEC in four groups based on their association with severe forms of clinical infection. STEC strains carrying the eae gene, particularly those of serogroups O157, O26, O111, O103, O145, O121, O45 and more recently O80 (top 8 serogroups), are usually monitored worldwide, whereas eae-negative STEC strains that are less clinically significant are not surveyed. Screening food enrichment broths with classical genetic markers (stx, eae) can overestimate the presence of highly virulent STEC, causing needless disruption and costs for food producers. Recently the updated MLG5C reference method introduced additional genetic markers (espK, espV) in the detection scheme to improve specificity and effectiveness of priority STEC detection in foodstuffs. This study, conducted on beef samples with a new method supporting the regulatory USDA-FSIS MLG5C.04 method, showed that 92% of the stx-positive samples carry stx2 alone or in association with stx1. Among the stx2-positive samples, stx2a and/or stx2d subtypes dominate. Introduction of espK, espV markers on 868 stx+/eae+ beef enrichment broths reduced the number of presumptive positive results by 31%, compared to the ISO/TS 13136:2012 reference method. Subsequent analysis of the presumptive positives combining the O-group and the eae-subtype provided also a significant reduction of the number of the presumptive positive for the top 8 eae-positive STEC serogroups; and showed that O26, O103 and O157 were the most prevalent ones. Regarding the stx+/eae- samples, which are proportionally extremely predominant in beef as compared with the stx+/eae+ samples, 65% of them were positive for the serogroups monitored in this study (O91, O171, O174, O148, O146, O128 O113 and O104). The high occurrence of serogroup O113 observed in beef samples is not corroborated by the clinical data reported in France. Routine testing of beef samples should be revised to prioritize a hierarchical surveillance system based only on high risk STEC (STEC carrying the eae gene) and not on all STEC. This approach would provide Food Business Operators a significant improvement, saving time and costs while maintaining a high level of product safety.